Novel polythiophene based nanofibers obtained by simultaneous electrospinning and UV - KAHRAMAN, MEMET VEZİR (ELSEVIER SCIENCE SA, 2013)
In this study, photo cross-linked thiophene based nanofibers were prepared by utilizing UV and electrospinning technique at the same time. For this purpose 3-(ethyl acrylate) thiophene (AC-TP) and 3-( ethyl maleate) thiophene (MA-TP) were synthesized and polymerized to have Poly[3-(ethyl acrylate) thiophene] (P(AC-TP)) and Poly[3-(ethyl maleate) thiophene] (P(MA-TP)). The chemical structures of the synthesized monomers and polymers were characterized by Fourier transform infrared spectroscopy (FT-IR) and nuclear magnetic resonance spectroscopy (NMR) techniques. P(AC-TP) and P(MA-TP) polymers were mixed with PVA solutions. By utilizing UV and electrospinning technique at the same time, photo cross-linked thiophene based nanofibers were prepared. The thermal properties of nanofibers and polymers were examined by thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). The morphology of nanofibers was investigated by scanning electron microscopy (SEM). The results showed that as the amount of conducting polymer increased in the formulations, the average diameter of prepared nanofibers decreased. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Nanofiber; Photo cross-linked; Electrospinning; Polythiophene; Conducting polymer; POLYMER NANOFIBERS; OPTICAL CHARACTERIZATION; BENDING INSTABILITY; FIBERS; ELECTROPOLYMERIZATION; COMPOSITES